Evaluation of polymeric coatings and primers against chloride ingress in concrete - Aguiar, J. L. Barroso de (2007)
Nowadays, it is common knowledge that the biggest degradation of concrete is caused by outside to inside actions. Penetration of moisture, active gases and aggressive ions, as well as mechanical, physical and chemical causes frequently act together. A low porosity and low permeability of concrete to penetration of moisture and gases are the first lines of defence against several deterioration mechanisms. One of the possible ways to protect the concrete is using coatings and primers that act as a barrier against the environment. The effect of polymeric coatings and primers on the prevention of chloride ingress in concrete is studied. The chloride diffusion coefficients are determined by means of the CTH rapid method, in which chloride flow is forced with an electrical potential difference. Three polymers – silicone, acrylic and epoxy – were applied on normal and high performance concretes. The measured diffusion coefficients are compared. The importance of the measured differences is visualised by a life time prediction of the different combinations of concretes and polymers, with a concrete cover of 50 mm. Although all polymers improved the system performance against chloride ingress, the best results were found for the epoxies used.